Avaliação da assistência farmacêutica no município de Uruguaiana, RS - Bittencourt, Raqueli Altamiranda (2014)
Introduction: The Pharmaceutical Assistance (PA) is a set of actions for the promotion, protection and recovery of health. It has the medicine as essential input, combined with structure, people and technology, with the user as the greatest beneficiary. The main objectives of the PA are facilitating access to essential medicines and promote their rational use. Objective: To evaluate the situation of the municipality of Uruguaiana PA - RS, using prescribing indicators, assistance and service recommended by WHO and the Self-Assessment Instrument (IAPAF - Instrumento de Auto-Avaliação) proposed by Ministry of Health to evaluate the management skills and planning the AF service. Methods: Cross-sectional study, from a total of 650 interviews and observations between june-september/2013, in 11 Basic Health Unit and Central Pharmacy. The analyzed prescribing indicators were: average number of medications per visit; percentage of drugs prescribed by generic name; percentage of antibiotics prescribed; percentage of prescriptions containing injectable drugs and percentage of prescription drugs listed on the Municipal List of Essential Medicines. Although the indicators on the service were checked about availability of the Municipal List of Essential Medicines in all services surveyed and the availability of a list of key-medicines. The IAPAF was applied along the responsible pharmacists for Basic Pharmacy and warehouse of medicines. The stages of development for each step of PA were ranked from 1 to 3, where the level 1 was the least and the 3 was the best developed. Results: The number of drugs per prescription ranged from 1 to 10, with a mean of 1.7. The percentage of drugs prescribed by generic name and listed in the Municipal List of Essential Medicines was 75.5% and 67.7% respectively; in 9.7% were antibiotics prescriptions. The average appointment time was 6 minutes; 51.4% of users had attended their prescription; only 18.9% of patients fully understand the prescription. From 24 items analyzed in IAPAF, 12 were in stage 1 and 12 in stage 2. Conclusions: Because there is no Pharmacy or Therapeutics Committee, no use of the epidemiological profile for scheduling of medicines and pharmaceutical inputs, and no following the Good practices for Storage, Transportation, Distribution and Dispensing, there is no proper planning and management of PA in the municipality, and it may cause unnecessary expense and ineffectiveness of the health system. The average appointment time, far below from the recommended by WHO, may be influencing the lack of understanding of the prescription.